Analysis of Bio-Coke Proximate from Sago Drugs and Patchange Waste - Isa, La; Asmin, La Ode; Dedyerianto, Dedyerianto (Lambung Mangkurat University Press, 2024)
Bio-coke organic waste Sago dregs and Patchouli waste are produced by the pyrolysis method. In this study, proximate analysis of bio-coke was carried out with different comparisons of the composition of sago dregs and patchouli waste. Making bio-coke begins with cleaning and then drying the sago pulp and patchouli waste under direct sunlight. The pyrolysis process uses an initial temperature of 110 0C which is maintained for 15 minutes. Then the temperature was set at 600 0C maintained for 15 minutes and cooled at room temperature. The quality of bio-coke was obtained from a proximate analysis consisting of the value of water content, ash, volatile matter, fixed carbon, and calorific value. The results showed that the highest calorific value was a composition ratio of 5:1, which was 8,727.84 Cal/gr, with the lowest moisture content, volatile matter, and ash content, namely 2.24%; 30.74%; and 3.69%, and the highest bound carbon content is 63.3%.